Individual-specific relationship between external training and match load and creatine-kinase response in youth national team soccer players - Schuth, G.; Szigeti, G.; Dobreff, G.; Pasic, A.; Gabbett, T.; Szilas, A.; Pavlik, G. (Sports Health: A Multidisciplinary Approach, 2023)
Background: Previous studies have examined the relationship between external load and creatine-kinase (CK) response at the team level. This study aimed to build individualized CK prediction models for elite youth national team soccer players.